Antimicrobial, Anthelmintic Activities and Characterisation of Functional Phenolic Acids of Achyranthes aspera Linn.: A Medicinal Plant Used for the Treatment of Wounds and Ringworm in East Africa - Ndhlala, Ashwell R.; Ghebrehiwot, Habteab M.; Ncube, Bhekumthetho; Aremu, Adeyemi O.; Gruz, Jiří; Šubrtová, Michaela; Doležal, Karel; du Plooy, Christian P.; Abdelgadir, Hafiz A.; Van Staden, Johannes (Frontiers in Pharmacology, 2015)
Achyranthes aspera Linn. (Amaranthaceae) commonly known as Prickly Chaff flower (English) is traditionally used for treating a number of ailments. Different parts of the plant are used in treating wounds and ringworm in East Africa and elsewhere for a number of ailments. In this study, leaf extracts of A. aspera collected from two different geographical locations (Ciaat, Eritrea and Ukulinga, South Africa) were evaluated for antibacterial, antifungal, anthelmintic activities and the plant characterised for functional phenolic acids as well as protein binding capacity. The pathogens used in the tests were, two Gram-negative (Escherichia coli and Klebsiella pneumoniae), two Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus), a filamentus yeast-like fungus (Candida albicans) and a free-living nematode (Caenorhabditis elegans). The water and acetone extracts of the samples collected from Ciaat exhibited good antibacterial, antifungal and anthelmintic activity (MIC < 1 mg/ml) except the water extract against E. coli which showed moderate activity. In contrast, the extracts collected from Ukulinga exhibited moderate to weak activities except for the acetone (aq.) extracts which had good activity against some of the tested organisms. UHPLC-MS/MS revealed variation in the levels of some functional phenolic compounds, with rutin, chlorogenic acid and genistein not being detected in the extracts from Ukulinga. The variation was also observed in the protein binding capacity, which could offer a predictive wound healing model. All extracts from plant samples collected at Ciaat expressed significant dominant potency compared to similar extracts from Ukulinga.